Delving into the Sea of Meaning: Representations of Lexical and Grammatical Meaning in the Poem Ilaika by Imam Syafi'i - Irvan Muhamad Faza (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2025)
The main issue raised in this study is how the meanings of words in Imam Syafi'i's poem Ilaika contribute to forming a profound aesthetic and religious message. This study aims to analyze the lexical and grammatical meanings contained in Imam Syafi'i's poem Ilaika. The poem Ilaika is a classic Arabic literary work with high aesthetic and religious value. Through semantic analysis, it is hoped that the deeper meanings contained in each word and sentence structure in the poem can be revealed. This study uses a qualitative descriptive approach. The data analyzed is the text of the poem Ilaika. Data collection techniques were carried out through literature study and text analysis. Data analysis was carried out by identifying keywords, examining their lexical meanings, and analyzing the grammatical structure of the sentences. The theory used in this study is semantic theory, specifically lexical and grammatical semantics. Lexical semantics relates to the meaning of words individually, while grammatical semantics relates to the meaning formed from the relationship between words in a sentence. Based on the analysis presented, it can be found that each stanza in Imam Syafi'i's ilaika poem has two meanings, namely lexical meaning and grammatical meaning. There are three types of words that were found, namely nouns, verbs, and adjectives. The contribution of this research is to provide a more comprehensive understanding of Imam Syafi'i's poetry from a linguistic perspective.